"Fast SCR" reaction over Sm-modified MnOx-TiO2 for promoting reduction of NOx with NH3 - Gao, Chen; Shi, Jian-Wen; Fan, Zhaoyang; Wang, Baorui; Wang, Yao; He, Chi; Wang, Xinbo; Li, Jun; Niu, Chunming (Applied catalysis. A, General, 2018)
[Display omitted] •Sm was used as a dopant to modify MnOx-TiO2 for the first time.•Sm-modification broadened the temperature window for the SCR of NOx with NH3.•The effects of Sm addtion on catalytic performance and mechanism were disclosed.•The de-NOx over Sm-modified MnOx-TiO2 followed E-R and L-H mechanisms.•“Fast SCR” reaction over Sm-modified MnOx-TiO2 above 200 °C was discovered. A series of Sm-modified MnOx-TiO2 (SMT) catalysts are prepared and characterized. The results show that the introduction of Sm can effectively restrain the crystallization process of MnOx and TiO2, enhance the specific surface area, increase the surface concentration of chemisorbed oxygen species and the amount of strong surface acid sites, and reduce the surface concentration of Mn4+. The catalytic performances of the SMT catalysts are evaluated by the selective catalytic reduction (SCR) of NOx with NH3. It is found that SMT-0.3 catalyst (a 0.3 mol rate of Sm/Mn) exhibits a 100% NOx conversion in a wide operating temperature window from 180 to 390 °C, and a 100% N2 selectivity from 120 to 390 °C under a GHSV of 36,000 h−1, which is obviously better than MnOx-TiO2 without Sm addition. In-situ DRIFT spectra reveal that, at low temperature (below 200 °C), absorbed NH3 species can react with gas-phase NO over MnOx-TiO2 catalyst following Eley-Rideal (E-R) mechanism, while the NH3-SCR of NO over SMT-0.3 follows both E-R and Langmuir-Hinshelwood (L-H) mechanisms. However, at high temperature (above 200 °C), the SCR reaction over MnOx-TiO2 is via “standard SCR” process, but the SCR reaction over SMT-0.3 is through “fast SCR” reaction.